Experimental study of R1234yf as a drop-in replacement for R134a in an oil-free refrigeration system. (5th May 2019) - Li, Zhaohua; Liang, Kun; Jiang, Hanying
Highlights: R1234yf was compared with R134a in a novel oil-free refrigeration system. For given pressure ratio, mass flow rate of R1234yf is higher than R134a. Evaporator pressure drop for R1234yf is higher than R134a due to higher friction. CoP of R1234yf is 20% lower than R134a when condenser temperature is 40 °C. Specific mass flow rate of R1234yf decreases with increasing condenser temperature. Abstract: R1234yf is a synthetic refrigerant with global warming potential (GWP) of 4 and similar thermodynamic properties to R134a. This paper experimentally compares the performance of R1234yf with R134a in an oil-free vapour compression refrigeration (VCR) system. The oil-free VCR system consisting of oil-free linear compressors, an off-the-shelf condenser and an evaporator with an electric heater avoids the impact of oil lubricant on the heat transfer so that the two refrigerants can be appropriately compared with each other. Experiments for two refrigerants were carried out for compressor strokes of 9–13 mm, operating frequency of 32–38 Hz, pressure ratios of 2–4, and condenser temperatures of 40–50 °C with refrigerant charge of 250 g. The experimental results show that the coefficient of performance (CoP) of R1234yf is 20% lower than R134a with condenser temperature of 40 °C and evaporator temperature of 0 °C. The volumetric efficiency of R1234yf is 5% lower than R134a with condenser temperature of 40 °C and evaporator temperature of −1.5 °C. Results of evaporator pressure drop, superheat, power input, and cooling capacity are also reported.